Сравнительный анализ налоговых систем европейских стран в контексте интеграционных процессов - Ваниева, Э.А. (Культура народов Причерноморья, 2013)
The article is sacred to the problems of harmonization of the tax system of Ukraine as compared to some European countries. The basic theoretical questions of harmonization and integration of the tax system are considered. The estimation of level of adaptation and prospect of harmonization of the tax system of Ukraine and other European countries is Given. For a comparative analysis the tax systems of France, Spain, Germany, Canada, Great Britain, Romania and Italy were in-process considered. For comparison of the tax systems for basis an income tax on the profits of physical persons, income tax were taken, tax enterprises value-added and excises. The tax system of Ukraine is imperfect, has a row of defects and problem questions which need further decision.